Influence of surface and intermolecular interactions on the properties of supported polyoxometalates. Issue 12 (1st March 2023) - Primera-Pedrozo, Oliva M.; Tan, Shuai; Zhang, Difan; O'Callahan, Brian T.; Cao, Wenjin; Baxter, Eric T.; Wang, Xue-Bin; El-Khoury, Patrick Z.; Prabhakaran, Venkateshkumar; Glezakou, Vassiliki-Alexandra; Johnson, Grant E.
Abstract : The vibrational and electronic properties of supported polyoxometalates determine their suitability for potential applications as molecular qubits. Abstract : Polyoxometalates (POMs) with localized radical or open-shell metal sites have the potential to be used as transformative electronic spin based molecular qubits (MQs) for quantum computing (QC). For practical applications, MQs have to be immobilized in electronically or optically addressable arrays which introduces interactions with supports as well as neighboring POMs. Herein, we synthesized Keggin POMs with both tungsten (W) and vanadium (V) addenda atoms. Ion soft landing, a highly-controlled surface modification technique, was used to deliver mass-selected V-doped POMs to different self-assembled monolayer surfaces on gold (SAMs) without the solvent, counterions, and contaminants that normally accompany deposition from solution. Alkylthiol, perfluorinated, and carboxylic-acid terminated monolayers were employed as representative model supports on which different POM-surface and POM–POM interactions were characterized. We obtained insights into the vibrational properties of supported V-doped POMs and how they are perturbed by interactions with specific surface functional groups using infrared reflection absorption and scattering-type scanning near-field optical microscopy, as well as tip enhanced Raman spectroscopy. Different functional groups on SAMs and nanoscale heterogeneity are both shown to modulate the observed spectroscopic signatures. Spectral shifts are also found to be dependent on POM–POM interactions. The electronic structure of the V-doped POMs was determined in the gas phase using negative ion photoelectron spectroscopy and on surfaces with scanning Kelvin probe microscopy. The chemical functionality and charge transfer properties of the SAMs are demonstrated to exert an influence on the charge state and electronic configuration of supported V-doped POMs. The geometric and electronic structure of the POMs were also calculated using density functional theory. Our joint experimental and theoretical findings provide insight into how V substitution as well as POM-surface and POM–POM interactions influence the vibrational properties of POMs.